THE IMPACT OF USING PROJECT-BASED LEARNING METHOD TO IMPROVE WRITING SKILLS ON NARRATIVE TEXT OF THE EIGHTH-GRADE STUDENTS’ OF SMP NEGERI 7 TARAKAN - Dhea P, Errita; Rianto, Agus; Astuti, Crisyanti Windi; Nurdiana, Nurdiana (Borneo Journal of English Language Education, 2022)
The objective of this research was to find out whether there was any significant difference in students’ writing skill before and after being taught using the Project Based Learning method in learning narrative text at the eighth-grade students of SMP Negeri 7 Tarakan. The design of this research was pre-experimental research. The population in this research was all of the eighth grade students at SMP Negeri 7 Tarakan. The sample in this research was 31 students. The sample was chosen by using a purposive sampling technique. The class for treatment was VIII 3. It consisted of 31 students. The steps in this research were pre-test, treatment, and post-test. In the pre-test, the students were asked to answer the writing test. After giving the pre-test, the researcher gave treatment. The treatment class was taught by using Project Based Learning method. After giving the treatment, students were asked to answer the writing test in post test. In analysing the data, the researcher was used paired sample t-test in SPSS 24.0. The result of this study showed that there was different mean score between pre-test and post-test. It was proven by the result of students’ mean score from pre-test was 48.00 and 65.29 in the post test. It indicates that the improvement of the students’ mean score was 17.290. The result t-value is higher than t-table (7.478 2.042). It proves that the students’ writing skill in narrative text improved after giving the treatment. The result of sig (2 tailed) 0.000 is lower than 0.05, it means that the Project Based Learning method can give any contribution to the students’ writing skill. It can be concluded that using Project Based Learning method is impact to improve the students’ writing skill in narrative text at the eighth-grade students of SMP Negeri 7 Tarakan.